KEBAHAGIAAN PADA PEREMPUAN - Miwa Patnani, M.Si., Psi (Jurnal Online Psikogenesis, 2012)
Abstract.Every people in the world, both men and women, want to reach happiness all the time. With the variety of roles that women lived, seems indeed tend to be more prone to have depression and mental disorders. Therefore, it is very important to discuss how to improve the happiness of women, so that women are able to undergo a variety of their role optimally. In order to increase the happiness of women, first thing to do is understanding an overview of happiness on women, including those things that become a source of happiness, and the happiness of the component that most frequently present in a woman's happiness. This research aims to know the description of happiness in women based on age differences, marital status and employment status. The benefits of this research are getting a picture of happiness on females, so that later it can be deduced what are things that can be done to increase the happiness in women. This research is qualitative research with the research subject is a number of 22 women aged 18-62 years in the area of Jakarta, Bogor, Depok, Tangerang, and Bekasi. The selection of subjects is carried out by using an incidental sampling technique. Data collecting tool used was a demographics data questionnaires and happiness questionnaires. Happiness questionnaire in this study was used to measure the source of happiness, feeling of happiness levels and components of happiness. The results showed that the most important source of happiness on the women is family. The level of the highest feeling of happiness was found in women with the age range of 30-39 years. Meanwhile, for the components of happiness were consistently in supporting the happiness is a positive cognition and control.Keywords: source, happiness, women.Abstrak.Kebahagiaan adalah hal yang ingin dicapai oleh semua orang, baik laki-laki maupun perempuan. Dengan berbagai peran yang dijalani, perempuan tampaknya memang cenderung lebih mudah mengalami depresi dan gangguan mental. Oleh karena itu, sangat penting untuk didiskusikan adalah bagaimana upaya meningkatkan kebahagiaan pada perempuan agar kaum perempuan mampu menjalani berbagai perannya dengan optimal. Untuk dapat meningkatkan kebahagiaan pada kaum perempuan, terlebih dahulu harus dipahami gambaran kebahagiaan pada kaum perempuan, termasuk hal-hal apa saja yang menjadi sumber kebahagiaan dan komponen kebahagiaan yang paling sering ada dalam kebahagiaan seorang perempuan. Penelitian ini bertujuan untuk mengetahui gambaran kebahagiaan pada kaum perempuan berdasarkan perbedaan usia, status pernikahan dan status pekerjaan. Manfaat dari penelitian ini adalah diperolehnya gambaran tentang kebahagiaan pada kaum perempuan, sehingga nantinya dapat disimpulkan apa saja hal-hal yang dapat dilakukan untuk meningkatkan kebahagiaan pada kaum perempuan. Penelitian ini merupakan penelitian kualitatif dengan subyek penelitian adalah sejumlah 22 orang perempuan berusia 18 – 62 tahun di wilayah Jakarta, Bogor, Depok, Tangerang, and Bekasi. Pemilihan subyek dilakukan dengan menggunakan teknik incidental sampling. Alat pengumpul data yang digunakan adalah kuesioner data demografi dan kuesioner kebahagiaan. Kuesioner kebahagiaan dalam penelitian ini mengukur sumber kebahagiaan, tingkat rasa bahagia dan komponen kebahagiaan. Hasil penelitian menunjukkan bahwa sumber kebahagiaan pada kaum perempuan yang paling penting adalah keluarga. Tingkat rasa bahagia yang paling tinggi ditemukan pada kaum perempuan dengan rentang usia 30-39 tahun. Sementara untuk komponen kebahagiaan yang konsisten dalam mendukung kebahagiaan adalah kognisi yang positif dan pengendalian.Kata kunci: sumber, kebahagiaan, perempuan.